Assessment of Mediterranean Diet Regimen Knowledge among University Employees with Functional Gastrointestinal Disorders - Najm, Massara Abdullah; Mohammed, Tahseen Rajab (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): To assess knowledge-related Mediterranean diet regimen among the University of Baghdad employees’ with functional gastrointestinal disorders.Methods: A cross-sectional design was carried out at the University of Baghdad in Bab-Almudam region for the period between August 20th 2022 to November 20th 2022. A non-probability sampling was used among (80) employees with functional digestive system disorders. A study instrument was constructed to collect data of knowledge-related Mediterranean diet regimen, which consists of two parts. The first part: socio-demographic characteristics such as: (age, gender, marital status, level of education, living arrangement) and the second part related to employees knowledge: a (45) questions divided into three domains: a (20) questions on the functional digestive system disorders; 13 questions regarding Mediterranean diet; and a (12) questions about the effect of the Mediterranean diet on functional gastrointestinal disorders. Data were analyzed using IBM SPSS version 25. Descriptive and Inferential statistics were utilized to summarize the results.Results: The study indicated that employees had knowledge deficits (95%) about the Mediterranean diet regimen.Conclusion: The study showed that there is a lack of employees’ knowledge about the Mediterranean diet regimen.Recommendations: The study recommends establish Mediterranean diet educational programs for persons with functional digestive disorders to learn how to deal with these disorders, and to improve their adherence to treatment and a healthy diet, in cooperation with the Nutrition Research Institute.